Κριτική θεώρηση της εκτίμησης περιβαλλοντικού κινδύνου, ως εργαλείο για την εκτίμηση περιβαλλοντικών επιπτώσεων στα πλαίσια άσκησης περιβαλλοντικής πολιτικής στην Κύπρο - Γιατρού, Μιχάλης (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος,Τεχνολογικό πανεπιστήμιο Κύπρου, 2013)
This thesis discusses the importance of Environmental Risk Assessment, as part of a comprehensive Environmental Impact Assessment in Cyprus. Summarizing the directives and regulations that have been adopted into national law of Cyprus which create a strong foundation of environmental policy. Including extensive reference to an internationally recognized institutional tool, the Environmental Impact Assessment (EIA). The EIA is the major means of environmental control technical projects and activities and applies to all developed countries to prevent environmental damage. The EIA procedure, through the methodology, tools and steps that it follows, contribute effectively to sustainable development. The main objective of this study was to determine the utility of the institution of the Environmental Risk Assessment (ERA) as a tool of EIA. As a result, the risk is determined and the procedures and stages of assessment and control, assessment methods, risk management and risk analysis system are indicated. Finally, as a conclusion of this study resulting the significant contribution of the ERA in EIA, as both institutions when are applied together as interrelated and mutually complementary increase the potential to be exerted a more comprehensive environmental policy.
Keywords: Sustainable development; Developed countries